Including Legumes in Bermudagrass Pastures - J. L. Moyer; L. W. Lomas (Kansas Agricultural Experiment Station Research Reports, 2020)
Bermudagrass is a productive forage species when intensively managed. However, it has periods of dormancy and requires proper management to maintain forage quality. Legumes in a bermudagrass sward could improve forage quality and reduce fertilizer usage; however, legumes are difficult to establish and maintain with the competitive grass. Clovers can maintain survival once established in bermudagrass sod, and may be productive enough to substitute for some N fertilization. This study was designed to compare dry cow performance on a bermudagrass pasture system that included ladino and crimson clovers (Legume) vs. bermudagrass alone (Nitrogen). Use of legumes in wheat-bermudagrass pastures did not affect summer cow gains in 2019, but did reduce the quantity of nitrogen fertilizer required.
Keywords: bermudagrass; grazing; legumes; ladino clover; crimson clover; interseeding